2006
DOI: 10.1016/s0929-6646(09)60264-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Mandibular Prognathism

Abstract: Mandibular prognathism (MP) or skeletal Class III malocclusion with a prognathic mandible is one of the most severe maxillofacial deformities. Facial growth modification can be an effective method of resolving skeletal Class III jaw discrepancies in growing children with dentofacial orthopedic appliances including the chincup, face mask, maxillary protraction combined with chincup traction and the Fränkel functional regulator III appliance. Orthognathic surgery in conjunction with orthodontic treatment is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 48 publications
0
52
0
1
Order By: Relevance
“…20,22,23 Although a number of etiological factors have been found to contribute to mandibular morphology, genetic factors play a significant role. 33 Bailey 34 found that 30 genes can affect the morphogenesis of the mandible in mice. Different sites of GHR and new candidate genes must be examined to explain the relationship between different phenotypes and genetic variants as well as to understand the effects of genetic factors in the multifactorial etiology of MP.…”
Section: Relationship Between Mp and Ghr Gene Polymorphismsmentioning
confidence: 99%
“…20,22,23 Although a number of etiological factors have been found to contribute to mandibular morphology, genetic factors play a significant role. 33 Bailey 34 found that 30 genes can affect the morphogenesis of the mandible in mice. Different sites of GHR and new candidate genes must be examined to explain the relationship between different phenotypes and genetic variants as well as to understand the effects of genetic factors in the multifactorial etiology of MP.…”
Section: Relationship Between Mp and Ghr Gene Polymorphismsmentioning
confidence: 99%
“…Sagittal split ramus osteotomy (SSRO) and intraoral vertical osteotomy (IVRO) are common strategies for the treatment of mandibular prognathism patients (Chang et al, 2000). Both surgical techniques are well established, and each has risks and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In treating prognathism, surgeons, including dentists, strive to restore oral and maxillofacial function and aesthetics (Chang et al, 2006). Complications such as neurosensory disturbance (NSD) in the teeth, gingiva, lips, and cheeks may occur after surgical procedures such as sagittal split ramus osteotomy (SSRO) (van Merkesteyn et al, 2007;Yoshioka et al, 2010) because of injury to the inferior alveolar nerve (IFAN).…”
Section: Introductionmentioning
confidence: 99%